Substantiation of Parameters of Working Body of the Combined Unit for Repeated Crops - Nasritdinov Akhmadzhon Abdukhamidovich; Djurayev Ismoilxuja Kadir ugli; Haydaraliyev Otabek Habibulloevich; Toshboyeva Maftuna Qurvonali Qizi (International Journal on Orange Technologies, 2021)
In article the substantiation technological and design data depth of immersing, a corner of a point of a disk, diameter of a disk of the adaptation to a general purpose plough is considered.